Effect of Companion Presence on Maternal Satisfaction During Neuraxial Catheter Placement for Labor Analgesia: A Randomized Clinical Trial. Issue 1 (March 2020) - Morell, E.; Peralta, F.M.; Higgins, N.; Suchar, A.; Fitzgerald, P.; McCarthy, R.J.
Abstract : ( Int J Obstet Anesth . 2019;38:66–74) Neuraxial labor analgesia is an effective and common choice for labor pain management, with the procedure being performed in the labor room under sterile conditions. While some hospitals ask the patient's companion to leave the room during epidural placement, some studies have found that the presence of a companion can affect both the patient's and companion's anxiety level. This study performed at a teaching hospital aimed to investigate the effect of companion presence during combined spinal epidural catheter placement on maternal satisfaction with the neuraxial procedure.